Biomarkers in predicting mortality from cardiovascular events in patients with heart failure and an implanted cardioverter-defibrillator - N. N. Ilov; O. V. Petrova; D. K. Tverdokhlebova; I. R. Karimov; A. A. Nechepurenko; S. A. Boytsov (Рациональная фармакотерапия в кардиологии)
Aim. To study the role of blood biomarkers in predicting death from cardiovascular events in patients with heart failure with reduced ejection fraction (HFrEF) within one year after cardioverter defibrillator (ICD) implantation.Material and methods. This one-center observation study included 384 HFrEF patients (men, 84%, NYHA class III – 74%, NYHA class IV – 7%), who underwent prospective observation for 1 year after ICD implantation. The study of the original panel of modern biomarkers (blood electrolytes, C-reactive protein, creatinine, soluble growth stimulation expressed gene 2 (sST2), N-terminal pro-brain natriuretic peptide (NT-proBNP), galectin-3), allowing to evaluate HF pathogenesis was conducted. Based on the blood creatinine concentration, the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula was used to estimate the glomerular filtration rate (GFR).Results. In a one-year observation, the primary endpoint was recorded in 35 patients (11%). Single-factor logistic regression showed 3 biomarkers with the greatest predictive potential (p<0,01), related to the occurrence of the investigated endpoint. The concentration of potassium and NT-proBNP, the GFR (CKD-EPI) was included in the multi-factor predictive model with diagnostic efficiency of 68% (sensitivity of 60%, specificity 71%). It was shown that the cardiovascular death risk increased by 2,64 (OR=2,64; 95% CI: 1,28-5,46; p=0,007) at GFR <60 ml/min/1,73 m2 and increased by 3,32 (OR=3,32; 95% CI: 1,26-8,73; p=0,012) at NT-proBNP >2000 pg/ml.Conclusion. The study of blood biomarkers is promising and in demand for the prediction of adverse outcomes of HF. According to the data obtained, the factors «GFR <60 ml/min/1,73 m2» and «NT-proBNP >2000 pg/ml» may be relevant for one-year mortality prediction.